Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Motivasi Belajar Siswa Kelas IV B Sekolah Dasar Negeri 219/IV Alam Barajo Jambi (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
The Discovery Learning model has advantages, including fostering a sense of enjoyment in students due to the excitement of discovery that always leads to success. This encourages students to direct their own learning activities, engaging their minds and motivation during the learning process in class. This research aims to improve the learning motivation of fourth-grade students at Elementary School 219/IV Alam Barajo Jambi through the application of the Discovery Learning model. This study uses a Classroom Action Research (CAR) method with two cycles. The results show that the application of the Discovery Learning model can enhance student learning motivation, marked by increased activeness, interest, and awareness in the learning process. This research implies that the Discovery Learning model can be an alternative for teachers to improve student learning motivation in elementary schools. Based on observations, student learning improved by 16% from cycle I to cycle II, while teacher activity increased by 15%. The learning completeness rate rose from 2.3% (pre-cycle) to 68.3% (cycle I) and reached 89.4% (cycle II). These findings demonstrate that the Discovery Learning model effectively enhances the learning motivation of fourth-grade students at Elementary School 219/IV Alam Barajo Jambi in Pancasila Education learning.